Sustainable Development Goals: Their Impacts on Forests and People - Katila, Pia; Pierce Colfer, Carol J.; de Jong, Wil; Galloway, Glenn; Pacheco, Pablo; Winkel, Georg (Life Sciences, 2019)
A global scientific assessment of the impacts of Sustainable Development Goals (SDGs) implementation on forests and related socioeconomic systems. It discusses the potential trade-offs among the SDGs, as well as the potential for synergies. An invaluable book for academics, students and decision-makers interested in links between sustainable development, forests and people. This title is available as Open Access via Cambridge Core.